Optimalisasi Application Programming Interface (API) Dalam Penjualan Cake Berbasis Web Menggunakan Metode User Centered Design (UCD) - Ananda Sustantiara; Agung Triayudi; Ira Diana Solihati (STMIK Budi Darma, 2023)
The rapid development of science and technology corresponds to the progress of human civilization and has contributed to increasing human needs in various areas of life, one of which is the need for communication and information. Speed and accuracy of data are, of course, very necessary to fulfil these needs. In this research, which was conducted in a pastry shop in Jakarta, there are many things that can be developed, considering that the system that is operated is still traditional. Therefore, a web-based system is being developed that can help advance the ongoing business. Advances in technology make users take advantage of the convenience it provides for the things they do. Therefore, technological advances have increased time efficiency and sales through a website where customers can easily order or buy cakes from home without coming to the store in person. The current process of recording sales is no longer done manually but has been integrated into the system automatically. This study's web-based information system for selling cakes was designed based on User Centered Design (UCD) method and User Experience Questioner (UEQ) method for users' convenience viewing web pages. The developed cake sales web-based information system is tested based on the User Experience Questioner (UEQ) method to support user comfort with website appearance. Based on the test results, an average (Mean) of 1.52 was obtained and the system development is able to meet the user needs and provide positives impressions.